DISTRIBUTION OF METALS IN CISANGGARUNG ESTUARY SEDIMENT, WEST JAVA, INDONESIA - Budiyanto, Fitri; Lestari, - (Marine Research in Indonesia, 2014)
Volcanic activities have inï¬? uenced the Cisanggarung estuary in western Cirebon Regency, altering metalÂ concentrations in the bottom sediment. Observation of metal content in the ocean there was carried out in AugustÂ 2009. Sediment samples were collected at 16 stations along the Cisanggarung coastline. The aim of this work wasÂ to determine the spatial distribution of Cd, Cu, Pb and Zn in the sediment of the Cisanggarung estuary. SedimentÂ was destructed using 3 acids: nitric acid, chloride acid and peroxide acid, which was then analyzed by Flame AtomicÂ Absorption Spectrophotometry based on the US EPA 3050b method. The highest concentrations of Cd, Cu, Pb andÂ Zn in the sediment were 0.73 mg/kg dry weight, 31.4 mg/kg dry weight, 23.9 mg/kg dry weight and 143 mg/kg dryÂ weight, respectively. The metals in the sediment had accumulated near the shoreline, up to ï¬ ve kilometers awayÂ from the river mouth, indicating that terrestrial area and sediment fractions inï¬? uenced their distribution.